PKM UPAYA PEMAHAMAN BAHASA BAGI GENERASI MUDA SEBAGAI PENANDA KELAS SOSIAL: TI NJAUAN SOSIOPRAGMATIK DI KELURAHAN BAWAH DUKU KOTO BARU KABUPATEN SOLOK SUMATERA BARAT - Lubis, Anita Angraini (CV. Alfa Pustaka, 2024)
The purpose of this service is a sociopragmatic study to explore the use of language used by speakers. either in the form of advice or good advice from parents to children, from someone to colleagues, and so on. Then, it will also discuss writing errors related to foreign languages ​​for prestige value, but the goal is even less due to writing errors due to lack of understanding regarding writing in English. Another purpose is to increase the selling value of a product which indirectly reflects the social class of a society. The method used in data collection is the listening method, namely listening to the use of language to obtain lingual data (Sudaryanto, 1993:133). This method is described using several techniques, namely tapping techniques, observing and observing skillfully, observing freely, recording, and note-taking techniques. The result of this dedication is that the language will create diversity, which is influenced by various factors. One of them is that language users who are heterogeneous with different backgrounds will continuously be able to more or less influence the language used. The existence of social levels in society is enough to contribute to the variety of languages ​​that appear in the midst of society.